Effectiveness of Modification Aids in High Jump Learning - Achmad Karim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aimed to determine the effectiveness of modified learning aids in improving the high jump ability using the Fosbury Flop technique among twelfth-grade students at SMA Negeri 11 Makassar. A quantitative approach with a quasi-experimental method and pretest-posttest control group design was employed. The population consisted of 120 twelfth-grade students, with a sample of 30 students selected through purposive sampling and divided into two groups 15 students in the experimental group receiving instruction with modified learning aids and 15 students in the control group receiving conventional instruction. The intervention was conducted over eight weeks with two sessions per week. The research instrument was a high jump performance test with three jump attempts, and data were analyzed using Paired Samples t-Test, Independent Samples t-Test, and N-Gain Score calculation. The results revealed that the experimental group improved by an average of 15.3 cm from 105.3 cm to 120.6 cm which was statistically significant (t = 21.161; p = 0.000), while the control group improved by only 8.7 cm from 104.8 cm to 113.5 cm (t = 14.653; p = 0.000). The between-group comparison via Independent Samples t-Test yielded t = 2.387 with a significance value of 0.024 (p < 0.05), confirming a significant difference between the two groups. N-Gain Score calculations indicated that the experimental group achieved a score of 0.68 (moderate category) while the control group obtained only 0.19 (low category). This study concludes that the use of modified learning aids is significantly more effective in improving students' high jump performance than conventional instruction, and successfully brought the average student achievement above the minimum competency standard set by the curriculum. These findings recommend that physical education teachers adopt modification-based learning approaches as a primary strategy in athletics instruction, particularly in schools with limited standard sports facilities.